Biografi dan Karya Intelektual Tan Malaka: Studi Historis-Faktual Tokoh - Tohis, Reza Adeputra (Historia Islamica: Journal of Islamic History and Civilization, 2023)
This article is a study of the biography and intellectual work of Tan Malaka as a figure. The study of the biography of Tan Malaka will look at factual life and the form of its important role. Through the study of the intellectual work of Tan Malaka, it will be seen how the factuality of the birth of the work and the changes it creates. For this reason, the method of philosophical research is used with the technique of historical-factual study of figures. This technique focuses on the thoughts of one philosopher or figures both on a specific topic in his work and on his entire work. The sociological theory of knowledge is used as an analytical approach to uncover the factuality of Tan Malaka's biography and intellectual work. The result is that the biography of Tan Malaka is formed on the factual situation of colonialism, institutions, interactions with various people, and various languages and Sciences. While the intellectual work of Tan Malaka is the result of his struggle with various factualities.